Introduction to Digital Libraries - Fox, Edward A.; Chen, Yinlin (2021 ACM/IEEE Joint Conference on Digital Libraries (JCDL), 2021)
This tutorial is a thorough and deep introduction to the Digital Libraries (DL) field, providing a firm foundation: covering key concepts and terminology, as well as services, systems, technologies, methods, standards, projects, issues, and practices. It introduces and builds upon a firm theoretical foundation (starting with the '5S' set of intuitive aspects: Streams, Structures, Spaces, Scenarios, Societies), giving careful definitions and explanations of all the key parts of a 'minimal digital library', and expanding from that basis to cover key DL issues. Illustrations come from a set of case studies, including from multiple current projects, including with the application of natural language processing and machine learning to webpages, tweets, and long documents. Attendees will be exposed to four Morgan and Claypool books that elaborate on 5S. Further, new material will be added on building digital libraries using container and cloud services, on developing a digital library for electronic theses and dissertations, and methods to integrate UX and DL design approaches.